2017
DOI: 10.1021/jacs.7b07930
|View full text |Cite
|
Sign up to set email alerts
|

Helix Propensities of Amino Acid Residues via Thioester Exchange

Abstract: We describe the use of thioester exchange equilibria to measure the propensities of amino acid residues to participate in helical secondary structure at room temperature in the absence of denaturants. Thermally or chemically induced unfolding has previously been employed to measure α-helix propensities among proteinogenic α-amino acid residues, and quantitative comparison with precedents indicates that the thioester exchange system is reliable for residues that lack side chain charge. This system allows the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…39 The observations of Watanabe et al raise the possibility that signal transduction mediated by GLP-1 is promoted by the accessibility of a reverse turn centered on Gly10, rather than restriction to the α-helical secondary structure observed via cryo-EM for this region of receptor-bound GLP-1. 40 Studies with peptide and protein model systems indicate that replacing Gly with L-Ala stabilizes a right-handed α-helical conformation by up to 1 kcal/mol, 4143 while replacing Gly with D-Ala destabilizes the α-helical conformation by up to 0.5 kcal/mol. 41…”
mentioning
confidence: 99%
“…39 The observations of Watanabe et al raise the possibility that signal transduction mediated by GLP-1 is promoted by the accessibility of a reverse turn centered on Gly10, rather than restriction to the α-helical secondary structure observed via cryo-EM for this region of receptor-bound GLP-1. 40 Studies with peptide and protein model systems indicate that replacing Gly with L-Ala stabilizes a right-handed α-helical conformation by up to 1 kcal/mol, 4143 while replacing Gly with D-Ala destabilizes the α-helical conformation by up to 0.5 kcal/mol. 41…”
mentioning
confidence: 99%
“…[15][16][17] Peptidomimetic compounds can recapitulate the structure and functiono fn atural AMPs while circumventing their susceptibility to protease degradation. [18] Beta-and g-peptides, [19][20][21][22][23][24][25][26][27][28][29][30][31][32] peptoids, [33][34][35][36] b-peptoids, [37,38] and oligoureas [39] have generated significant interesta sp otentialt herapeutic agents, especially since they can adopts table and predictables econdary structures and are anticipated to disturbt he bacterial cell membrane similarly to AMPs.O ur investigationsf ocus on the incorporationo fa za-b 3 -amino acids in natural peptides equences to modulate their bioavailability and activity.L inear and cyclic aza-b 3 -peptides can adopt well-definedc onformations stabilized by ah ydrogen-bond network leading to bifidic eightmembered pseudocycles forming hydrazino turns (N-N turns) in the solid state and in organic media. [40,41] Although the azab 3 -amino acid Ns tereocenter bearing the side chains is not fixed and can adopt the l or d configuration, the cyclic constraints ignificantly reduces the inversion rate at the Nc enter.…”
Section: Introductionmentioning
confidence: 99%
“…Peptidomimetic compounds can recapitulate the structure and function of natural AMPs while circumventing their susceptibility to protease degradation . Beta‐ and γ‐peptides, peptoids, β‐peptoids, and oligoureas have generated significant interest as potential therapeutic agents, especially since they can adopt stable and predictable secondary structures and are anticipated to disturb the bacterial cell membrane similarly to AMPs. Our investigations focus on the incorporation of aza‐β 3 ‐amino acids in natural peptide sequences to modulate their bioavailability and activity.…”
Section: Introductionmentioning
confidence: 99%
“…A first step toward that goal, involving the T variant containing β 3- homoalanine (β 3 -hAla) at two f positions, indicated that a β 3 -hAla residue within an α-helix-like conformation is 0.6 kcal/mol less favorable than an Ala residue within an α-helix. 7…”
mentioning
confidence: 99%
“…All β 3 residues mentioned so far are enantiospecifically derived from the corresponding L-α-amino acids ( S configuration) with retention of configuration. Inversion of configuration ( ent -β 3- hAla) leads to a decline in helix propensity of ≈ 0.7 kcal/mol, which is qualitatively consistent with but smaller than the decline in α-helix propensity reported for D-Ala ( R configuration) relative to L-Ala. 1b,7 The Aib residue ( gem -dimethyl substitution) has an α-helix propensity larger than that of Ala, 1b,11 but β 3,3 -hAib mani-fests a significantly lower helix propensity relative to β 3 -hAla.…”
mentioning
confidence: 99%